Survey of Awareness and Perceptions of Canadians on the Benefits and Risks of Clinical Trials. (September 2019) - Willison, Donald J.; Richards, Dawn P.; Orth, Alison; Harris, Heather; Marlin, Susan
Background: Little is known about the Canadian public's perspective regarding clinical trials. Methods: We surveyed 1602 Ontario and British Columbia residents to ascertain their understanding of and willingness to participate in clinical trials. Results: Clinical trials are regarded positively with overall perceptions that they provide societal and personal benefits. Most respondents were somewhat (49%) or very willing (19%) to participate in a clinical trial. This increased with age and level of education. It was also greater among those with poor or very poor health, those with multiple chronic conditions, and those who had previously been invited into a clinical trial, all of which were correlated with age. Still, there was room for improvement in awareness and understanding of clinical trials. Forty-three percent of those surveyed felt not very informed or not at all informed and 37% had no opinion regarding clinical trials. Respondents would most often turn to their treating physician if considering participating in a clinical trial and least often to social media. Conclusion: While Canadians' views about clinical trials are generally positive, they are somewhat muted and a significant minority feels poorly or not at all informed. They are less willing to participate in clinical research than Americans and are roughly equivalent to Europeans. While clinicians are the top choice for learning about clinical trials, they have little or no training and little time for this role. As we move toward integrating clinical trials into the practice setting, these issues of time, training, and resources must be addressed.